Dedicated breast PET for detecting residual disease after neoadjuvant chemotherapy in operable breast cancer: A prospective cohort study. Issue 4 (April 2018) - Sasada, Shinsuke; Masumoto, Norio; Goda, Noriko; Kajitani, Keiko; Emi, Akiko; Kadoya, Takayuki; Okada, Morihito
Abstract: Purpose: Diagnostic methods to evaluate the response to neoadjuvant chemotherapy (NAC) for breast cancer have not been established. Dedicated breast PET (DbPET) is a high-resolution molecular breast imaging method, and we investigated the capability of DbPET to predict residual primary tumors after NAC compared with whole-body PET (WBPET). Methods: Forty-five patients (47 tumors) underwent WBPET and ring-type DbPET after NAC, and the tumors were completely resected between January 2016 and March 2017. The pathological response was classified as complete remission (ypT0), residual intraductal disease (ypTis), or residual invasive disease (ypT ≥ 1). Standardized uptake value (SUV) and tumor-to-normal tissue ratio (TNR) were assessed. Results: Twelve patients achieved ypT0 and five developed ypTis. DbPET detected all cases of ypTis, and WBPET detected only one case of ypTis. The sensitivity, specificity, and accuracy of WBPET for ypTis and/or ypT ≥ 1 were 54.3%, 83.3%, and 61.7%, respectively, and those of DbPET were 77.1%, 83.3%, and 78.7%, respectively. In the ypT0/ypTis/ypT ≥ 1 groups, the median WBPET-SUV, DbPET-SUV, and DbPET-TNR was 1.0/0.9/1.1, 1.7/1.8/2.2, and 1.0/1.6/1.7 ( P  = .134, .077, and 0.008), respectively. Areas under the curves of WBPET-SUV, DbPET-SUV, and DbPET-TNR for predicting ypTis and/or ypT ≥ 1 were 0.610, 0.648, and 0.807, respectively. Conclusions: DbPET was more accurate than WBPET in detecting residual primary tumors after NAC, particularly intraductal carcinoma. TNR was the better parameter for pathological evaluation compared with SUV.